Effects of school organizational conditions on teacher professional learning in China: The mediating role of teacher self-efficacy. (September 2020) - Huang, Liang; Zhang, Ting; Huang, Yating
Highlights: Learning-centered leadership (LL) and learning opportunities (LO) positively impact teacher professional learning (TPL). However, the negative and direct effect of cultural barriers (CB) on TPL was not confirmed. Teacher self-efficacy had a significant and positive effect on TPL. Unexpectedly, LO had no significant impact on teacher self-efficacy. Particularly, teacher self-efficacy significantly mediated the effects of both LL and CB on TPL. Abstract: Current education reforms have increasingly advocated schools to create facilitative organizational conditions to promote teacher learning. However, limited research has examined the effects of different aspects of school organizational conditions on teacher professional learning in China. Using a sample of 339 primary and secondary school teachers in Shanghai, this study examined the effects of three aspects of school organizational conditions (i.e., learning-centered leadership, learning opportunities, and cultural barriers) on teacher professional learning in China, with a particular focus on the mediating role of teacher self-efficacy as an important psychological condition. The results showed that two aspects of school organizational conditions (i.e., learning-centered leadership and learning opportunities) had significant and positive effects on teacher learning. Teacher self-efficacy significantly mediated the effects of both learning-centered leadership and cultural barriers on teacher professional learning. Practical implications are also discussed.